Prospects of gas production from the vertically heterogeneous hydrate reservoirs through depressurization in the Mallik site of Canada - Hongwu Lei; Zhenjun Yang; Yingli Xia; Yilong Yuan (Energy Reports, 2022)
Natural gas hydrate (NGH) is a clean and efficient energy resource with extensive distribution in the permafrost regions and marine sediments. A few short-term production tests focusing on reservoir depressurization have been conducted in recent years. However, the long-term production performance and the transient evolution characteristics of reservoir properties are not well known. In this work, a more realistic hydrate-reservoir model that considers the heterogeneity of permeability, porosity and hydrate saturation is constructed, according to the available geological data at the Mallik site. The model is validated by reproducing the field depressurization test. The main purposes of this work are to evaluate the long-term gas production performance and to analyze the unique multiphase flow behaviors from the validated geologically descriptive hydrate-reservoir model. The results indicate that the long-term gas production through depressurization from hydrate reservoirs at the Mallik site is technically feasible, but the gas production efficiency is generally modest. The hydrate dissociation front in HBS is strongly affected by the reservoir heterogeneity and shows a unique dissociation front. The vertically heterogeneous HBS is beneficial for depressurization production compared to the massive hydrate reservoirs. Furthermore, the vertically heterogeneous hydrate-reservoir with low permeability of clay-layer can effectively block methane gas diffusion in the vertical direction. These emphasize that constructing realistic reservoir models is very important to accurately predict the hydrate production performance. At the end of 1-year depressurization, a total of 1.80 × 106 ST m3 of methane gas can be produced from the validated hydrate-reservoir, while which is far from the commercial value. In addition, reducing the production pressure in the wellbore is beneficial for increasing gas production volume, but is not conducive to improving the hydrate production efficiency at the Mallik site.